PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI UPT PUSKSEMAS LABUAN - Yulianti, Eneng; Azizi, Enji; Kusuma, Hero Wirasmara (LP2M Universitas Bina Bangsa, 2025)
This study aims to determine the effect of physical work environment and work discipline on employee performance. This study uses quantitative research object research at UPT Puskesmas Labuan with a population and sample of 75 respondents. Sampling using saturated sampling technique. Data in this study were taken using a questionnaire. The analysis techniques used validity test, reliability test, multiple linear regression analysis, classical assumption test, hypothesis test using SPSS version 27 application. The results of the analysis concluded that the Physical Work Environment Variable (X1) has a significant positive effect on Employee Performance (Y). Work Discipline Variable (X2) has a significant positive effect on Employee Performance (Y). The Physical Work Environment Variable (X1) and Work Discipline (X2) have a significant positive effect on Employee Performance (Y).